Cortico-cortical coupling in Parkinson's disease and its modulation by therapy. - Silberstein, P; Pogosyan, A; Kühn, A; Hotton, G; Tisch, S; Kupsch, A; Dowsey-Limousin, P; Hariz, M; Brown, P (2005)
The role of changes in inter-regional cortical synchronization in the pathophysiology of Parkinson's disease and the mechanism of action of dopaminergic therapy and high frequency subthalamic nucleus (STN) stimulation is unclear. We hypothesized that synchronization between distributed cortical areas would correlate with parkinsonism and that changes in synchronization with treatment would correlate with improvements in parkinsonism. To this end, we recorded scalp EEG in parkinsonian patients off treatment (16 patients, 31 sides) and then separately during high frequency stimulation (HFS) of the STN (16 patients, 31 sides) and following drug treatment (12 patients, 24 sides). All recordings were made at rest to avoid the confounding effects of differences in task performance. The motor Unified Parkinson's Disease Rating Scale (UPDRS) score was determined in each state. We found that EEG-EEG coherence over approximately 10-35 Hz correlated with the severity of parkinsonism, and reductions in cortical coupling over this frequency range with both l-dopa and STN stimulation correlated with clinical improvement. These results suggest that both dopaminergic therapy and STN stimulation may support the restoration of normal cortico-cortical interactions in the frequency domain. This mechanistic similarity may underscore the strong clinical correlation between the therapeutic effects of these treatment modalities.